Impact of a demand-side integrated WASH and nutrition community-based care group intervention on behavioural change: a randomised controlled trial in western Kenya. Issue 11 (24th November 2020) - Freeman, Matthew C; Ellis, Anna S; Ogutu, Emily Awino; Caruso, Bethany A; Linabarger, Molly; Micek, Katie; Muga, Richard; Girard, Amy Webb; Wodnik, Breanna K; Jacob Arriola, Kimberly
Abstract : Introduction: Growth shortfalls and diarrhoeal diseases remain a major cause of morbidity and mortality in low-income settings. Due to the multifaceted causes of undernutrition and the identified limitations of siloed nutrition programmes, improving the delivery of integrated water, sanitation, hygiene (WASH) and nutrition programming could improve child health. Methods: We conducted a cluster randomised trial in western Kenya to assess the impact on household behaviours of a novel, theory-informed and integrated WASH and nutrition intervention delivered through care groups as compared with the standard care group approach. We developed an intervention targeting practices relating to food hygiene, mealtime and feeding, and compound cleanliness, each using various behavioural change techniques to influence the uptake of targeted behaviours. Prespecified behavioural outcomes were verified through direct observation, 24 hours recall, and self-reported picture-based methods. Results: Compared with control households, a greater proportion of intervention households had a hygienic food preparation area (Risk double difference (RDD) 0.81, 95% CI 0.68 to 0.96), had stored food hygienically (RDD 0.76, 95% CI 0.58 to 1.00), had a functional handwashing station (RDD 0.64, 95% CI 0.56 to 0.74), provided a safe space for their child to play (RDD 0.73, 95% CI 0.56 to 0.96), and who fed their children thickened porridge (RDD 0.56, 95% CI 0.51 to 0.63) at endline. The proportion of children 6–24 months in intervention households consuming a sufficient diversity of foods (RDD 0.81, 95% CI 0.64 to 1.04) was higher than in control households; however, there was a non-significant increase in the percentage of pregnant and lactating women receiving an adequate diversity of foods in their diets (RDD 0.86, 95% CI 0.70 to 1.05) among intervention compared with control households at endline. Conclusion: Our integrated WASH and nutrition intervention resulted in important changes in behaviours. This theory-informed intervention could be added to existing care group programmes to considerable advantage.